Somebody else's body - Urge Overkill; Geffen Records (United States : Geffen Records, 1995)
Contains the track taken from the album Exit The Dragon.
g CD 1: Somebody Else's Body (edit) / (3:20) -- Somebody Else's Body (LP version) / (3:48).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Rock music